Conocimiento y cobertura vacunal sobre influenza y neumonía en adultos mayores del Centro de Salud El Cambio del cantón Machala. - Pardo Capa, Diana Thalía (2018)
The objective of this research is to determine the degree of knowledge and vaccination coverage on Influenza and Pneumonia in elderly people of the El Cambio del Cantón Machala Health Center. The World Health Organization estimates that the flu causes between 250,000 and 500,000 deaths each year, pneumonia also ranks third in the causes of mortality in elderly people and according to statistics more than 50% must be hospitalized for complications, that with the increase in age the immune system undergoes changes that lead to a greater severity of infectious diseases. The study is descriptive, cross-sectional and retrospective. The technique used to collect data for the documentary review to determine vaccination coverage, taking into account the total population of 1036 people over 65 years of age and the survey randomly applied to 130 patients who attended a medical check-up during the month of December 2017, with equality of percentages in men and women, the majority is between 65 and 69 years old, 72.3% have a medium level of knowledge about Influenza, pneumonia and vaccines, vaccination coverage of Influenza reaches 96.4% and of Pneumococcus 10%. Concluding that despite knowing about Influenza and Pneumonia in the coverage of vaccination against Pneumococcus, factors such as the vaccination scheme every five years, the cost of the biological and the lack of it. Key words: Adults, Knowledge, Vaccination coverage, Influenza, Pneumonia.